(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article metrology and standardization science modern trends, their economic in development place and importance Metrology measures accuracy, reliability and diversity to provide as a science focused on standardization and products, processes and services quality increase them mutual adaptation and technician obstacles eliminate to reach service does. In the article, Metrology and standardization in the global economy role, international in trade caught role, innovative in development importance, also in Uzbekistan this sector develop according to done increasing affairs analysis is made. From this, digital metrology, green standards, artificial to the intellect-based measurement systems such as new also see trends released.